PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PT.BPR BANK DAERAH KARANGANYAR (PERSERODA) YANG DIMEDIASI OLEH MOTIVASI - Arianto Pramudjadi; Subijanto; Woro Utari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
Arianto Pramudjadi, 2022. The influence of leadership style and work culture on employee performance of PT.BPR Bank Daerah Karanganyar (Perseroda) mediated by motivation. Postgraduate Program at Wijaya Putra University, Surabaya. This type of research is explanatory research, the research approach uses a quantitative approach, and data analysis uses Partial Least Square (PLS). The research sample was 65 people. The aims of this research are 1). To find out and analyze the direct influence of leadership style on employee performance at PT.BPR Bank Daerah Karanganyar (PERSERODA) 2). To find out and analyze the direct influence of work culture on the performance of employees of PT.BPR Bank Daerah Karanganyar (PERSERODA) 3). To find out and analyze the direct influence of leadership style on the motivation of PT.BPR Regional Bank Karanganyar (PERSERODA) 4). To determine and analyze the direct influence of work culture on the motivation of PT.BPR Regional Bank Karanganyar (PERSERODA) 5). To find out and analyze the direct influence of motivation on employee performance at PT.BPR Bank Daerah Karanganyar (PERSERODA) 6). To determine and analyze the direct influence of leadership style on employee performance with motivation as a motivation variable PT.BPR Bank Daerah Karanganyar (PERSERODA) 7). To determine and analyze the direct influence of work culture on employee performance with motivation as a motivation variable PT.BPR Bank Daerah Karanganyar (PERSERODA).The results showed that: Based on the results of the hypothesis testing research, it can be seen at the significance level, if the p-value 0.05,